Multiple Roles of c-di-GMP Signaling in Bacterial Pathogenesis - Valentini,M; Filloux,A (Annual Review of Microbiology, 2019)
The intracellular signaling molecule cyclic di-GMP (c-di-GMP) regulates the lifestyle of bacteria and controls many key functions and mechanisms. In the case of bacterial pathogens, a wide variety of virulence lifestyle factors have been shown to be regulated by c-di-GMP. Evidence of the importance of this molecule for bacterial pathogenesis has become so great that new antimicrobial agents are tested for their capacity of targeting c-di-GMP signaling. This review summarizes the current knowledge on this topic and reveals its application for the development of new antivirulence intervention strategies.